Modelling Electrical Resistance Tomography Using COMSOL and Matlab for Crack Detection Analysis - Mohd Muji, Siti Zarina; Zaini, Khairul Akmal; Mohmad Ameran, Hanis Liyana; Abdul Wahab, Yasmin; Roslee, Muhammad Nuriffat; Ambar, Radzi (Journal of Electronic Voltage and Application, 2020)
Electrical resistivity tomography (ERT) is designed for prediction on electrode polarization, potential drop near current supply and electrode that proximate to phantom, electrode size, width, and length. ERT is felicitous to be utilized for an experiment on material that is conductive like concrete. The objective of this study is to model ERT sensor in two-dimension by utilizing COMSOL Multiphysics software. The study uses opposite method of electrode excitation for the analyses of the output voltage in the presence of air holes detection. The result of the electric field from the COMSOL is used further in the Matlab to reconstruct the image in the form of 64x64 pixels using Linear Back Projection (LBP) algorithm. ERT model is tested with the presence of one air hole or more. The same goes to the output voltage whenever the air holes are incremented. In conclusion, the opposite electrodes activation is suitable method to be considered because it produces the linear relation between the output voltage and the air holes.